Caught in the Act of Quenching? -- A Population of Post-Starburst Ultra-Diffuse Galaxies - Loraine Sandoval Ascencio; M. C. Cooper; Dennis Zaritsky; Richard Donnerstein; Donghyeon J. Khim; Devontae C. Baxter (The Open Journal of Astrophysics)
We report the discovery of post-starburst ultra-diffuse galaxies (UDGs), identified through spectroscopic analysis with KCWI at the Keck II Telescope. Our analysis is based on a sample of 44 candidate UDGs selected from the Systematically Measuring Ultra-Diffuse Galaxies (SMUDGes) program. Our measured spectroscopic redshifts reveal $\sim 85%$ of the entire KCWI sample exhibit large physical sizes ($R_{e} \gtrsim 1~{\rm kpc}$) and low surface brightnesses ($24 \lesssim μ_{0,g} \lesssim 25$ mag arcsec^-2^) which categorize them as UDGs. We find $20%$ of the confirmed UDG population contain post-starburst (or K+A) features, characterized by minimal to no emission in H$β$ indicative of quenched star formation and a predominant presence of spectral A-type stars. In surveying the local environments of the post-starburst UDGs, we find that nearly half are isolated systems, which is unusual given that isolated UDGs are most commonly found to be star-forming. Two of these systems reside $2-3~R_{\rm vir}$ away from potential nearby massive hosts ($M_{\star} >10^{10}~M_{\odot}$), indicating the absence of environmental influence. These post-starburst UDGs may represent systems experiencing star formation feedback such that a recent burst may lead to (at least temporary) quenching. Overall, our results highlight the potentially diverse quenching pathways of UDGs in the local Universe.